Hubungan Dukungan Sosial Dengan Kualitas Hidup Ibu Hamil Berisiko Tinggi - Muhammad Faruq Faiz Hawari; Diah Eko Martini; Heny Ekawati (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Background: High-risk pregnant women are a vulnerable group at risk of health problems during pregnancy, childbirth, and the postpartum period. Their quality of life is greatly influenced by social support, especially from family. Unfortunately, many high-risk pregnant women do not receive optimal social support, resulting in a low quality of life. Methods: This study used a quantitative approach with 43 respondents selected through consecutive sampling. Data were collected using a social support and quality of life questionnaire, then analyzed using the Spearman Rho test. Results: The results showed a significant relationship between social support and quality of life in high-risk pregnant women, with a significance value of p = 0.035 and a correlation coefficient of r = 0.322. This indicates that the higher the social support received by high-risk pregnant women, the better their perceived quality of life. Conclusion: There is a significant relationship between social support and quality of life. Therefore, the higher the social support received by high-risk pregnant women, the better their quality of life.